QUALITY OF LIFE AND COVID-19 PHOBIA OF CANCER PATIENTS RECEIVING CHEMOTHERAPY IN A STATE HOSPITAL DURING PANDEMIC: CROSS SECTIONAL STUDY - HIDIROĞLU, SEYHAN (My University, 2022)
Objective: COVID-19 pandemic has become a global public health problem and led to phobia among people. There is also no doubt that the COVID-19 pandemic had a great impact on the quality of people\"s lives. The goal of this study was to assess the factors that might be affecting the quality of life and COVID-19 phobia of the cancer patients receiving chemotherapy. Materials and Methods: This cross-sectional study was conducted between November 2021 and April 2022 in an outpatient chemotherapy unit within a state hospital in Istanbul. Participants\" data was gathered by a questionnaire that had 3 components: participants\" characteristics, the COVID-19 phobia scale, and the WHOQOL-BREF scale. Results: The results showed that perceived economic status, education level, having comorbidities, having a caregiver and who is the caregiver had an impact on the Quality of Life, and people who have an acquaintance who died due to COVID-19 had higher COVID-19 phobia total score. Furthermore, it was seen that as the age or COVID-19 phobia total score increased, each component of the Quality of Life score decreased. Conclusions: Quality of life and COVID-19 phobia of cancer patients were observed to be inversely proportional in chemotherapy receiving patients in a state hospital in Istanbul.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Cancer; Quality of life; COVID-19; Phobia.